2018
DOI: 10.5114/pm.2018.78559
|View full text |Cite
|
Sign up to set email alerts
|

Premature ovarian insufficiency – hormone replacement therapy and management of long-term consequences

Abstract: Premature ovarian insufficiency (POI) correlates with increased risk of cardiovascular diseases, osteoporosis, genitourinary syndrome, and other symptoms of prolonged oestrogen deprivation. Properly selected therapy improves the quality of women’s lives and reduces the risk of mortality. There is a wide spectrum of available oestrogen and progestogen formulations restoring proper levels of serum sex steroid hormones. The treatment should be implemented at recognition of the POI and continued to at least the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…POI is one of the causes of infertility, and the great challenge is that it is difficult to cure or reverse. In addition, patients with POI can often exhibit serious mental and physical problems [35,36]. And it was confirmed that imatinib could provide selective protection against CDDP induced ovarian injury [37].…”
Section: Discussionmentioning
confidence: 86%
“…POI is one of the causes of infertility, and the great challenge is that it is difficult to cure or reverse. In addition, patients with POI can often exhibit serious mental and physical problems [35,36]. And it was confirmed that imatinib could provide selective protection against CDDP induced ovarian injury [37].…”
Section: Discussionmentioning
confidence: 86%
“…POI is one of the causes of infertility, and the great challenge is that it is di cult to cure or reverse. In addition, patients with POI can often exhibit serious mental and physical problems [35,36]. One of the major causes is that chemotherapy drugs were applied to the treatment of childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with POI can often exhibit serious mental and physical problems. [29,30] Consequently, there is an urgent need to identify preventive diagnostic markers and effective treatments for POI patients. There is a growing body of evidence to suggest that microRNAs (miRNAs) are important regulators in the pathogenesis of POI.…”
Section: Discussionmentioning
confidence: 99%